INVESTIGATE OF INFLUENCE PERFORATED PLATE ON DETERMINATION OF TRANSVERSAL PERMEABILITY ON REINFORCED FIBER - Pereira, G. S.; Oliveira, C. P.; Souza, J. A. (Revista de Engenharia Térmica, 2024)
Polymeric composite materials can be build in different forms, resulting in different mechanical properties, with numerous industrial applications. Traditionally, they have been largely used in the automotive, naval and aerospace industries. A major concern in polymeric composites manufacture is related with the determination and control of the reinforcement and resin physical properties. They are responsible for the final composite mechanic properties and, if not correct defined, will result in defective composites. Reinforcement permeability is one of these physical properties that, in some cases, are difficult to be kept within the project specification. More specifically, for the case of the transverse permeability, its corrected determination is reported in literature as being considerably more difficult to experiment than the in-plane permeability. The most common experiment for transverse permeability determination is built with a cylindrical mold on which the reinforcement is positioned (and compressed) between two perforated plates. A fluid is forced transversely through the reinforcement, volumetric flow rate and pressure drop are measured, and the Darcy’s Law is used to determine the permeability. In this experiment, flow is assumed rectilinear, and the holes of the perforated plates are ignored in the Darcy equation. It is known that size, number e position of these holes may influence the permeability determination, however this problem is not commonly discussed in literature. In this work it is presented a numerical study about the influence of the geometry of the perforated plates on the corrected determination of the reinforcement transverse permeability. The reinforcement region is molded as a porous medium and the two fluid flow (air + resin) is formulated with the Volume of Fluid (VoF) method. GMSH software was used to created and discretize the geometry and OpenFOAM software, more specifically using the interFoam solver, was used to solve the flow problem, determining pressure drop and flow rate inside the mold. Results have shown that correct determination of the transverse permeability is highly dependent on perforate plates geometry.